Short Communication: Erythrocytes and leukocytes profiles of bottlenose dolphins (Tursiops aduncus) at conservation site - Aryani Sismin Satyaningtijas; AGUSTIN INDRAWATI; RIZKA F. SYARAFINA; TALITA F. MILANI; M. SURYAPUTRA; AINUL KHADIJA SALEEMA; DESRAYNI HANADHITA (Society for Indonesian Biodiversity, 2020)
Abstract. Satyaningtijas AS, Indrawati A, Syarafina RF, Milani TF, Saleema AK. 2020. Short Communication: Erythrocytes and leukocytes profiles of bottlenose dolphins (Tursiops aduncus) at conservation site. Biodiversitas 21: 3359-3363. Health monitoring of dolphins to ensure optimal welfare in human care is important. This study measured erythrocytes and leukocytes in seven bottlenose dolphins (Tursiops aduncus) as a parameter to assess physiological status in PT. Wersut Seguni Indonesia (WSI) Marine Mammals Conservation. Blood was sampled through the superficial veins of each tail fin for examination of erythrocytes and leukocytes using hemocytometer method. Differential leukocytes were observed using thin blood smears stained by Giemza. The purpose of this study to collect hematological value of captive bottlenose dolphins. The results showed values of erythrocytes was (5.14±0.56) x 106/mm3, (13.86±1.68) gr/dl for hemoglobin, and (44.29±2.69)% for hematocrit. The value for leukocytes were  (4.2 ± 0,82) x 103/mm3 , 63.14 ± 9.77% for lymphocytes, 3.57 ± 1.72% for monocytes, 31.57 ± 8.43% for neutrophils, 1.29 ± 1.60% for eosinophils and 0.14 ± 0.38% for basophils. The average of the seven bottlenose dolphins Neutrophil to Lymphocyte ratio (N/L) was 0.53.